THE IMPORTANCE OF APPLYING INNOVATIVE FOREIGN EXPERIENCE IN TEACHING TECHNICAL AND TACTICAL SKILLS TO VOLLEYBALL PLAYERS AT THE STAGE OF GENERAL PHYSICAL PREPARATION - M.R. Rahmonova (International Journal of Literature and Language Studies, 2026)
Significant changes are taking place in our country in the field of educating the younger generation, providing vocational training, and ensuring their intellectual and spiritual development. In particular, the application of modern technologies in education contributes significantly to improving the effectiveness of the teaching and learning process. This article highlights the importance of implementing a system that complies with international educational standards in the organization of volleyball training. It also discusses technical and tactical preparation in volleyball, the use of modular educational technologies in volleyball instruction, and their pedagogical significance and advantages.